"Rufinos" - living between the "Agreste" of Paraiba and the City of Rio de Janeiro: a discussion about their work, migration and quilombola’s condition - Souza, Vanessa Emanuelle; Batista, Mercia Rejane Rangel (Revista de Ciências Sociais, 2018)
This paper seeks to discuss the ways in which the residents of Quilombo Matão (Paraíba – Brazil) are experiencing situations related to migration and labor through an ethnographic research. Therefore, we focused on the different relations of work with the cities, relations that changed and became more essential to the survival of the group and their remaining in the same place. In a certain way, it is possible to present and discuss the relations between these historical processes and the situations experienced by the group, including in the condition of member of a black community from a rural area later known as a quilombo. Also, it was sought to reflect on the research conditions that were constructed and gave support to this analysis.